2019
DOI: 10.33265/polar.v38.3393
|View full text |Cite
|
Sign up to set email alerts
|

A gloomy future for light-bellied brent geese in Tusenøyane, Svalbard, under a changing predator regime

Abstract: Light-bellied brent geese in Tusenøyane, Svalbard J. Madsen et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previous studies also identified increases in densities of nest predators (Langgemach & Bellebaum, 2005; Panek & Bresiński, 2002), which probably resulted from habitat fragmentation (Chalfoun et al, 2002), availability of additional food resources from agriculture (Cove et al, 2014; Wood, 1998) and in some species also from changes in hunting practices (Panek & Bresiński, 2002). Moreover, introduction of new species by humans or expansion of their ranges due to climatic changes can locally increase the diversity of potential nest predators (Iverson et al, 2014; Kauhala & Kowalczyk, 2011; Madsen et al, 2019; Prop et al, 2015). Thus, the increase in nest predation intensity in passerines that we document here might have been the result of gradually increasing predation pressure caused by habitat fragmentation or changes in predator communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also identified increases in densities of nest predators (Langgemach & Bellebaum, 2005; Panek & Bresiński, 2002), which probably resulted from habitat fragmentation (Chalfoun et al, 2002), availability of additional food resources from agriculture (Cove et al, 2014; Wood, 1998) and in some species also from changes in hunting practices (Panek & Bresiński, 2002). Moreover, introduction of new species by humans or expansion of their ranges due to climatic changes can locally increase the diversity of potential nest predators (Iverson et al, 2014; Kauhala & Kowalczyk, 2011; Madsen et al, 2019; Prop et al, 2015). Thus, the increase in nest predation intensity in passerines that we document here might have been the result of gradually increasing predation pressure caused by habitat fragmentation or changes in predator communities.…”
Section: Discussionmentioning
confidence: 99%
“…If the presence of foraging bears in nesting bird colonies results in decreased nest attendance by incubating individuals, this will create additional foraging opportunities for avian predators and potentially lead to underestimates of total nest losses ultimately due to bears. As these types of interactions between foraging bears, avian predators and nesting prey species have been reported in multiple different Arctic regions (Barry 1967, Gaston and Elliott 2013, Iles et al 2013, Iverson et al 2014, Rode et al 2015, Madsen et al 2019, formal investigation into this interspecific foraging association and prey behavioural responses are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…One changing predator regime that has gained much attention is that of Arctic nesting birds and the increasing predation (Hanson 2006) of nests by polar bears Ursus maritimus (Donaldson et al 1995, Rockwell and Gormezano 2009, Prop et al 2013, 2015, Iverson et al 2014, Gormezano et al 2017, Madsen et al 2019, Barnas et al 2020, Dey et al 2020, Jagielski et al 2021a, b). While consumption of bird eggs by bears has been reported in the past (Canadian Wildlife Service 1992, Cooke et al 1995, Derocher 2012), climate‐induced loss of spring sea‐ice is increasing the amount of time bears spend on land in recent years resulting in more frequent overlap with the incubation period of Arctic nesting birds than has likely occurred in the past (Smith et al 2010, Iverson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common eiders are an ecologically and culturally significant species (Clyde et al, 2021;Henri et al, 2018), and our study provides insights on climate-induced changes in the predator community of eiders on East Bay Island. We demonstrated that avian predators capitalize on disturbance foraging by polar bears, and it is likely that these types of interactions are occurring in other nesting bird colonies where avian predators and polar bears co-occur (Gaston & Elliott, 2013;Madsen et al, 2019). Simulation models predict redistribution of nesting eiders to smaller colonies in response to polar bears (Dey et al, 2017), but this has not yet been shown empirically (Dey et al, 2020).…”
Section: Discussionmentioning
confidence: 87%